2010
DOI: 10.4161/sgtp.1.3.14724
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles for RhoA during T cell transendothelial migration

Abstract: t cells need to cross endothelial barriers during immune surveillance and inflammation. this involves t-cell adhesion to the endothelium followed by polarization and crawling with a lamellipodium at the front and contractile uropod at the back. t cells subsequently extend lamellipodia and filopodia under the endothelium in order to transmigrate. rho Gtpases play key roles in cell migration by regulating cytoskeletal dynamics and cell adhesion. we have found that the rho Gtpase rhoa is required for efficient t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…This site has been previously reported to regulate ARHGEF2 activity (40). Moreover, ARHGEF2-dependent RhoA activity also has been shown to regulate the uropod of migrating T cells (71), in accordance with the report by Vang et al (88) that PDE8 inhibition caused a decrease in T-cell motility. In the current study, the combination of PDEs 1, 7, and 8 showed the largest increase in ARHGEF2 phosphorylation.…”
Section: Biological Processes Regulated By Different Pde-regulatedsupporting
confidence: 77%
See 1 more Smart Citation
“…This site has been previously reported to regulate ARHGEF2 activity (40). Moreover, ARHGEF2-dependent RhoA activity also has been shown to regulate the uropod of migrating T cells (71), in accordance with the report by Vang et al (88) that PDE8 inhibition caused a decrease in T-cell motility. In the current study, the combination of PDEs 1, 7, and 8 showed the largest increase in ARHGEF2 phosphorylation.…”
Section: Biological Processes Regulated By Different Pde-regulatedsupporting
confidence: 77%
“…A number of the biological processes identified by GO analysis have been previously reported to be regulated by cAMP. These include mRNA splicing (64)(65)(66), spindle organization (67,68), fibroblast migration (69,70), lamellipodium assembly (71,72), apoptosis (73)(74)(75)(76), ATM signaling (77,78), gene silencing via microRNA (79)(80)(81)(82), T-cell selection (83), and cytoskeletal reorganization (84). This study suggests which molecular substrates might participate in the regulation of these processes.…”
Section: Biological Processes Regulated By Different Pde-regulatedmentioning
confidence: 99%
“…While a constitutively active form of Rac1 persists at cell contacts, a loss of both Rac1 and active Rac1 from newly formed MDCK cell contacts occurs within 5 min of E-cadherin recruitment [39]. RhoA activity would then increase and could result in membrane retraction via ROCK and myosin light chain (p-MLC) phosphorylation [40]. The mechanism determining which of the two RhoA pathways is activated at the leading edge is not known but may depend on the localization of effectors and/or the levels of RhoA activity [40].…”
Section: Discussionmentioning
confidence: 99%
“…RhoA activity would then increase and could result in membrane retraction via ROCK and myosin light chain (p-MLC) phosphorylation [40]. The mechanism determining which of the two RhoA pathways is activated at the leading edge is not known but may depend on the localization of effectors and/or the levels of RhoA activity [40].…”
Section: Discussionmentioning
confidence: 99%
“…Low molecular weight guanine-nucleotide-binding (G) proteins of the Ras superfamily, also known as small GTPases for their GTP hydrolysis activity, are single-subunit proteins activated by diverse extracellular stimuli and implicated in a number of crucial cellular processes including cell proliferation, differentiation, apoptosis, cytoskeletal organization, cell polarity, and vesicular trafficking (1)(2)(3)(4). G proteins act as molecular switches and cycle between a GDP-bound inactive and a GTPbound active conformation that regulate their ability to interact with downstream effectors and regulatory proteins.…”
Section: ؉mentioning
confidence: 99%